Action Is The Measure - Swing, Raymond (Tufts Archival Research Center, 2006)
Raymond Swing, an editor for "This I Believe," describes how the realization that most of his troubles were caused by ignorance led him to become more tolerant of others, and states his beliefs in his participation in the "All-Wisdom" of God, in his responsibility to change himself, and in the importance of extending to others the love and freedom which he desires for himself. Contains a short advertisement for This I Believe book (this essay included in the book).